2022
DOI: 10.1186/s12891-022-06049-3
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise reduction of bone mineral density increases the risk of cage subsidence in oblique lumbar interbody fusion patients biomechanically: an in-silico study

Abstract: Background Cage subsidence causes poor prognoses in patients treated by oblique lumbar interbody fusion (OLIF). Deterioration of the biomechanical environment initially triggers cage subsidence, and patients with low bone mineral density (BMD) suffer a higher risk of cage subsidence. However, whether low BMD increases the risk of cage subsidence by deteriorating the local biomechanical environment has not been clearly identified. Methods OLIF witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Therefore, anti-osteoporosis treatment should be considered an effective therapy to avoid subsidence risk. 29,30 Additional, previous studies confirmed that relatively flat endplates significantly diminish the incidence of subsidence. Consequently, the morphology of cage surface should be also taken into consideration when designing the next generation of cage, 23,24 which is also the future research direction of prevention of CS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, anti-osteoporosis treatment should be considered an effective therapy to avoid subsidence risk. 29,30 Additional, previous studies confirmed that relatively flat endplates significantly diminish the incidence of subsidence. Consequently, the morphology of cage surface should be also taken into consideration when designing the next generation of cage, 23,24 which is also the future research direction of prevention of CS.…”
Section: Discussionmentioning
confidence: 80%
“…From a biomechanical perspective, low BMD triggers stress concentration in surgical segment and increases the risk of a poor local biomechanical environment in OLIF patients. Therefore, anti‐osteoporosis treatment should be considered an effective therapy to avoid subsidence risk 29,30 . Additional, previous studies confirmed that relatively flat endplates significantly diminish the incidence of subsidence.…”
Section: Discussionmentioning
confidence: 93%